Buying the honor of thieves? Performance pay, political patronage, and corruption - Campbell, Jesse W. (International journal of law, crime and justice, 2020)
Corruption undermines government effectiveness and performance pay may be used as a "legal bribe" to encourage bureaucrats to act honestly. However, if performance pay is awarded based on loyalty rather than performance, its use may aggravate corruption rather than reduce it. Collusion is facilitated when patronage crowds out merit in the public sector recruitment process, and this study, therefore, tests whether the relationship between performance pay and corruption is conditioned by patronage-based recruitment. A model of corruption is estimated using data from an expert survey of performance pay usage in government in over 100 countries and both a survey-based measure of patronage and a multi-source patronage risk index. A series of cross-country regressions suggest that the effect of performance pay on corruption is negative when patronage is low but either non-significant or positive in countries where patronage pervades the recruitment process. This study demonstrates how a popular anti-corruption reform may interact with competing incentives embedded in the context of implementation to worsen corruption.